# Verify $a-(-b)=a+b$ for the following values of $a$ and $b$.(i) $a=21, b=18$(ii) $a=118, b=125$(iii) $a=75, b=84$(iv) $a=28, b=11$

#### Complete Python Prime Pack

9 Courses     2 eBooks

#### Artificial Intelligence & Machine Learning Prime Pack

6 Courses     1 eBooks

#### Java Prime Pack

9 Courses     2 eBooks

Given:

Some values of $a$ and $b$.

To do:

We have to verify whether $a\ -\ ( -b) \ =\ a\ +\ b$

Solution:

We know that,

$(-) \times (-) = (+)$

Therefore,

(i) $a = 21, b = 18$

This implies,

$a\ -\ (-b)\ =21\ -\ (-18)$

$=\ 21\ +\ 18$

$=\ 39$

$a+b=21+18$

$=39$

Hence, $a\ -\ ( -b) \ =\ a\ +\ b$.

(ii) $a = 118, b = 125$

This implies,

$a\ -\ (-b)\ =118- (-125)$

$=\ 118\ +\ 125$

$= 243$

$a+b=118+125$

$=243$

Hence, $a\ -\ ( -b) \ =\ a\ +\ b$.

(iii) $a = 75, b = 84$

This implies,

$a - (-b) =75 - (-84)$

$=\ 75\ +\ 84$

$=\ 159$

$a+b=75+84$

$=159$

Hence, $a\ -\ ( -b) \ =\ a\ +\ b$.

(iv) $a = 28, b = 11$

This implies,

$a - (-b) =28 - (-11)$

$=\ 28\ +\ 11$

$=\ 39$

$a+b=28+11$

$=39$

Hence, $a\ -\ ( -b) \ =\ a\ +\ b$.

Hence, we can see that in every case $a\ -\ (-b)\ =\ a\ +\ b$.

Updated on 10-Oct-2022 13:31:00